Summary of recommendations of the Team for Community Projects and National Extension Service and Views Expressed by the State Governments and The Central Ministries Concerned - Planning Commission (Planning Commission, 2000)
The governing consideration in distributing the functions between the village panchayats. the panchayat samitis anti the zila parishad will generally be that all the functions concerning a village within the jurisdiction of a village panchayat should be the responsibility of the village panchayat except for the functions involving similar interests of more than one village panchayat; these should be the responsibility of the panchayat samiti. Similarly, such functions of the panchayat samiti as may involve more than one panchayat samiti should be the responsibility of the zila parishad.
Planning Commission Government of India
Planning Commission Government of India